2017
DOI: 10.1016/j.fsi.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Who needs the hotspot? The effect of temperature on the fish host immune response to Tetracapsuloides bryosalmonae the causative agent of proliferative kidney disease

Abstract: Proliferative kidney disease (PKD) of salmonids, caused by Tetracapsuloides bryosalmonae may lead to high mortalities at elevated water temperatures. However, it has not yet been investigated how temperature affects the fish host immune response to T. bryosalmonae. We exposed YOY (young of the year) rainbow trout (Oncorhynchus mykiss) to T. bryosalmonae at two temperatures (12 °C and 15 °C) that reflect a realistic environmental scenario and could occur in the natural habitat of salmonids. We followed the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 49 publications
6
80
3
Order By: Relevance
“…In these studies, parasite intensity was significantly greater in kidneys of brown trout compared with rainbow trout, similar to the present study (Kumar et al, 2013), whereas only rainbow trout showed severe clinical signs of PKD in contrast to brown trout (Grabner & El-Matbouli, 2008). Reports have separately explored how temperature influences the development of T. bryosalmonae in either brown trout (Wahli, Bernet, Segner, & Schmidt-Posthaus, 2008) or rainbow trout (Bailey et al, 2017;), but they have not yet investigated the influence of temperature from the confirmation of infection onwards with a defined dose identical for both species, in these species, in a comparative fashion.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In these studies, parasite intensity was significantly greater in kidneys of brown trout compared with rainbow trout, similar to the present study (Kumar et al, 2013), whereas only rainbow trout showed severe clinical signs of PKD in contrast to brown trout (Grabner & El-Matbouli, 2008). Reports have separately explored how temperature influences the development of T. bryosalmonae in either brown trout (Wahli, Bernet, Segner, & Schmidt-Posthaus, 2008) or rainbow trout (Bailey et al, 2017;), but they have not yet investigated the influence of temperature from the confirmation of infection onwards with a defined dose identical for both species, in these species, in a comparative fashion.…”
Section: Discussionsupporting
confidence: 83%
“…In these studies, parasite intensity was significantly greater in kidneys of brown trout compared with rainbow trout, similar to the present study (Kumar et al., ), whereas only rainbow trout showed severe clinical signs of PKD in contrast to brown trout (Grabner & El‐Matbouli, ). Reports have separately explored how temperature influences the development of T. bryosalmonae in either brown trout (Wahli, Bernet, Segner, & Schmidt‐Posthaus, ) or rainbow trout (Bailey et al., ; Bettge, Wahli, Segner, & Schmidt‐Posthaus, ; Bettge, Segner et al., ), but they have not yet investigated the influence of temperature from the confirmation of infection onwards with a defined dose identical for both species, in these species, in a comparative fashion. By focusing on parasite kinetics, influence of temperature on the processes and differences between the two fish species, we provide a different perspective to earlier studies which focused on the development of clinical PKD (Bettge, Segner et al., ; Bettge, Wahli et al., ; Grabner & El‐Matbouli, ; Kumar et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune system response under the various treatments was assessed by measuring the organ somatic indices of two key immune organs in fish-the head kidney (HKSI) and spleen (SSI)-as well as the mRNA transcript levels of immune genes involved in the host response of rainbow trout to the infection by T. bryosalmonae. The selection of the genes was based on the findings reported by Bailey et al [51] and Gorgoglione et al [57] on the rainbow trout immune response to T. bryosalmonae infection.…”
Section: Immune System and Infection Statusmentioning
confidence: 99%
“…Infection intensity of the fish by the parasite reaches maximum values towards autumn, when the fish physiologically prepares for winter. Under the experimental conditions chosen in the present study, the parasite causes a long-term infection and corresponding immune response without causing gross mortalities [51,52]. All three chosen environmental stressors are real world stressors that co-occur in the aquatic habitats of salmonids.…”
Section: Introductionmentioning
confidence: 99%